Surrogates' Perceptions of Service Quality While Making Decisions for ICU Patients. (October 2019) - Gul, Senay; Turkman, Yasemin E.; Bakitas, Marie A.; Dionne-Odom, J. Nicholas
A qualitative secondary analysis was undertaken to identify aspects of health care service quality in an intensive care unit from the perspective of surrogate decision makers ( N = 19) who were making decisions for relatives at end of life. Directed content analysis was guided by the Donabedian model of health care quality. Nineteen participants averaged 59 years old and were over half female (53%) and patients' spouses (53%) and adult children (32%). Salient aspects of quality service included surrogate perceptions that clinicians conveyed honesty about the patient's condition and in an easily understandable way; staff were sensitive and responsive to emotions and practical needs; clinicians demonstrated a clear, confident understanding of the patient's condition; and support by clinicians was given for surrogates' choices. Surrogates also commented on the hospital and intensive care unit environment, including cleanliness, comfort, privacy, and noise level. Further research is needed to explore how decision-support strategies might include service quality concepts.